Identification and Functional Analysis of Three MAX2 Orthologs in Chrysanthemum1. Issue 5 (25th April 2013) - Dong, Lili; Ishak, Abdurazak; Yu, Jing; Zhao, Ruiyan; Zhao, Liangjun
Abstract: MORE AXILLARY BRANCHING 2 ( MAX2 ), initially identified in Arabidopsis thaliana, is a key regulatory gene in strigolactone signal transduction. Three orthologs of MAX2 were cloned from Dendranthema grandiflorum ( DgMAX2a, b, and c ). Each of the genes has an open reading frame of 2, 049 bp and encodes 682 amino acid proteins. The predicted amino acid sequences of the three DgMAX2s are most closely related to the MAX2 orthologs identified in petunia (PhMAX2A and PhMAX2B), and display the highest amino acid sequence similarity with PhMAX2A compared to other MAX2s. Expression analysis revealed that DgMAX2s are predominantly expressed in the stem and axillary buds. On a cellular level, we localized the DgMAX2a::GFP fusion protein to the nucleus in onion epidermal cells, which is consistent with the nuclear localization of MAX2 in Arabidopsis . The chrysanthemum DgMAX2a is able to restore the max2–1 mutant branching to wild‐type (WT) Arabidopsis, suggesting that it is a functional MAX2 ortholog. These results suggest that DgMAX2s may be candidate genes for reducing the shoot branching of chrysanthemum.